The obstacles to combat against COVID-19 pandemic and the remedies: Bangladesh scenario - Mst. Rashida Pervin (PAGEPress Publications, 2021)
Background: Bangladesh has been going through the austerity of the unique COVID-19 for more than a year like several other nations in the world in spite of concerted efforts taken by the government along with other concerned authorities who have advocated compulsory guidelines involving social distancing procedures accompanied by lockdown to have control over the pandemic. In this paper, the barriers faced by the government to protect people from the COVID-19 pandemic have been investigated. Also, the number of daily infected people against the number of daily tests has been underlined to comprehend the overall pandemic picture in Bangladesh.